2015
DOI: 10.13005/bbra/1797
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Short-term Plyometric Training Program on Sprint, Strength, Power and Agility Performance in non-athletic Men

Abstract: Plyometric training to increase physical ability and leads to increase of muscles power. The aim of the study was to assess the effects of short term plyometric training program on sprint, strength, and power and agility performance in non-athletic men. In this research, 40 non-athletic men (year 18-23) participated. The participants were chosen randomly and they participated in four tests strength (Swedish swimming, sit-ups), power (vertical jumps, Horizontal jumps), agility (Illinois Agility Test, T Agility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Jumping performance was assessed in 24 of the included studies . Within‐group improvements in jumping performance were ranging from 3.4% to 26.3% in the PLY groups vs −6% to 8% in the control groups, following 4‐12 weeks of intervention (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Jumping performance was assessed in 24 of the included studies . Within‐group improvements in jumping performance were ranging from 3.4% to 26.3% in the PLY groups vs −6% to 8% in the control groups, following 4‐12 weeks of intervention (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Aalizadeth et al showed a significant reduction in non‐athletic men of −12.1% in 30 m sprint time. This study used a “low‐frequency‐low‐volume” approach, with PLY being performed only 1 d/wk for 5 weeks consisting of 80‐100 impacts per week.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations